Biomaterials in the Treatment of Anal Fistula: Hope or Hype? - Scoglio, Daniele; Walker, Avery S.; Fichera, Alessandro (Clinics in Colon and Rectal Surgery, 2014)
Anal fistula (AF) presents a chronic problem for patients and colorectal surgeons alike. Surgical treatment may result in impairment of continence and long-term risk of recurrence. Treatment options for AFs vary according to their location and complexity. The ideal approach should result in low recurrence rates and minimal impact on continence. New technical approaches involving biologically derived products such as biological mesh, fibrin glue, fistula plug, and stem cells have been applied in the treatment of AF to improve outcomes and decrease recurrence rates and the risk of fecal incontinence. In this review, we will highlight the current evidence and describe our personal experience with these novel approaches.
Keywords: anal fistula; biologic mesh; fibrin glue; fistula plug; bio-LIFT; stem cells